Comparison of Epidural or Regional Analgesia and Patient-controlled Analgesia: A Critical Analysis of Patient Data by the Acute Pain Service in a University Hospital. Issue 8 (August 2016) - van Boekel, Regina L. M.; Vissers, Kris C. P.; van de Vossenberg, Glenn; de Baat-Ananta, Mira; van der Sande, Rob; Scheffer, Gert Jan; Steegers, Monique A. H.
Abstract : Objectives: A large number of patients still experience pain after surgery. This study investigates if epidural or regional analgesia (continuous infusion peripheral nerve blocks [CPNB]) provide superior pain relief compared with patient-controlled analgesia (PCIA) and identifies the incidence of minor and major adverse effects or complications of these techniques. Materials and Methods: Prospectively collected data of postoperative patients from an online data registration system of a special dedicated nurse-based acute pain service were analyzed. The acute pain service consultations were documented from January 2008 to August 2013 in a university hospital in The Netherlands. Results: An analysis was applied on data of 12, 399 consecutive patients. Results showed that patients who received epidural analgesia and CPNB reported lower pain scores than those who received PCIA, after undergoing the same procedures. In addition, pain scores at rest were significantly lower than movement-evoked pain scores, in abdominal surgery. Severe nausea was mostly observed in patients with PCIA and itching was most common in patients with epidural analgesia. Opioid-induced respiratory depression was found in 5 patients with PCIA. Discussion: Epidural analgesia and CPNB provide better pain relief to patients than PCIA, especially in dynamic pain scores of patients. Evaluating real patient data on every patient visit is important for further improvement of the quality of postoperative pain management. Pain scores may vary widely between patients with similar surgical procedures. Therefore, we recommend that future research focuses on personalized pain measurement and pain management, to improve clinical practice more intensely. Abstract : Supplemental Digital Content is available in the text.